Pengembangan Kurikulum Berbasis Life Skill di TK Ceria Demangan Yogyakarta - Qonita Faizatul Fitriyah; Salpina Salpina; Rts Desi Paramitasari (IKIP Siliwangi, 2022)
Curriculum have an important role in education, to produce quality human resources. However, the application of curriculum in Indonesia is still minimal in terms of human resource quality, because it only emphasizes the academic field and emphasizes theory rather than practice. One of the things that indicates a person has a high level of quality is that has the abilty of life abilities. So it is legitimate if an educational institution wants to apply a life skill based curriculum such as Ceria Demangan Kindergarten Yogyakarta. Therefore this study aims to: 1) find out how the process of apllying life skill based curriculum in Kindergarten Ceria Demangan, 2) find out how the development of aspects of child development with the implementation of life skill based curriculum. The research method used is a qualitative descriptive method with data collection techniques using observation, interviews, and documentation techniques. The results of this study indcate that the implementation, planning and evaluation of life skill bassed curriculum cannot be separated from the cooperation of parents, teachers, principals, and studends.